SHELF-LIFE AND QUALITY CHARACTERISTICS OF SMOKED CATFISH (Clarias gariepinus) STORED IN COMPOSITE PACKAGING MATERIALS (2012)
Smoking and drying are major methods of processing and preserving fish in Nigeria. However, inadequate packaging using cartons, baskets, jute and mat bags with transparent polyethylene are the most common which offer little protection against external agents and has been a major challenge. There is dearth of information on the developments of appropriate fish packaging thereby limiting fishery preservation to small scale business. The use of composite packaging materials for storage of smoked catfish were investigated. Packaging materials were laminated into six opaque composite packages: Polyethylene-Cardboard (PC), Cardboard-Polyethylene (CP), Polyethylene-Cardboard-Polyethylene (PCP), Polyethylene-Paper (PPa), Paper-Polyethylene (PaP) and Polyethylene-Paper-Polyethylene (PPaP) and Polyethylene (P) as control. Thickness, weight, Impact Resistance Weight (IRW), water and oil absorption rates of the packaging materials were determined using standard methods. Catfish (Clarias gariepinus) of six months age harvested at Kano State Department of Fisheries, Wudil, were killed, gutted, cleaned, salted, weighed and dried in a smoking kiln. Proximate, microbial and sensory analyses (9 Hedonic scale) of dried catfish were determined at the start of the experiment and monthly for six months in storage under ambient conditions. Data were analyzed using descriptive statistics and ANOVA at p = 0.05. The thicknesses of the composite materials ranged from 0.23 to 0.46 mm while control was 0.27 mm. The weights and IRW ranged from 15.0 to 34.7 g and 25.0 to 50.0 g for the composite respectively, while the corresponding results for control were 18.9 g and 35.0 g. The water and oil absorption rates for the composite were 0.8 to 10.0 g/cm2/min and 2.5 to 10.9 g/cm2/min, while the control had 0.3 and 0.4 g/cm2/min respectively. The crude protein, moisture content, fat, ash and crude fiber of the fish (332.48 ± 62.91 g) stored in the composite ranged from 65.7 to71.9 %; 8.8 to 10.5 %, 11.0 to 12.2 %; 5.3 to 6.3 % and 2.5 to 3.3 %, while their corresponding values in the control were 64.4 %, 9.6 %, 12.4 %, 5.7 %, 3.6 % respectively at six months as compared to their baseline values of 68.4 %, 7.3 %, 12.5 %, 6.4 %, 1.8 %. Total bacterial and yeast/mould counts of the stored catfish in composite were from 10.0 x 10-4 cfu/g to 16.0 x 10-4 cfu/g and 5.0 x 10-4 cfu/g to 19.0 x 10-4 cfu/g; while that in the control were 18.0 x 10-4 cfu/g and 17.0 x 10-4 cfu/g respectively at six months. The baseline values for total bacterial and yeast/mould counts were 2.0 x 10-4 cfu/g and 0. The overall acceptance scores for samples in composite ranged from 4.8 to 7.0, while that of control was 4.6 with baseline value of 7.0. Fish stored in PPaP and PCP had best results in crude protein, moisture content, fat, ash, crude fiber, total bacterial, yeast/mould count and sensory evaluation for the stored catfish. PPaP and PCP packages maintained the quality attributes of stored catfish compared to others. Their usages would not only add-value to fish business in Nigeria but improve market integrity.